International law and transition to peace in Colombia : assessing jus post bellum in practice - Rojas-Orozco, César (Theory and practice of public international law ;, 2021)
"In International Law and Transition to Peace in Colombia, César Rojas-Orozco analyses the role of international law in transition from armed conflict to peace, by using the analytical framework of jus post bellum and Colombia as a case study. While contemporary attention to jus post bellum has focused on its theoretical development and regarding international warfare, this book is the first work to comprehensively assess the concept in practice and in the context of a non-international armed conflict. Discussing the creative formulas adopted in Colombia to conciliate international legal requirements and the practical needs of peace, the book offers concrete elements to understand the concept of jus post bellum as a framework to guide other transitions around the world"--